ENDOVASCULAR ANEURYSM REPAIR FOR INTACT AND RUPTURED ABDOMINAL AORTIC ANEURYSMS: SHOULD WE EXPECT MORE COMPLICATIONS AFTER R-EVAR? - Oliveira Pinto, José (2018)
Introduction: Endovascular Aneurysm repair (EVAR) for ruptured abdominal aortic aneurysm (r-AAA) has been increasingly advocated due to short term benefits. Survival after discharge seems to be similar between EVAR for rAAA (r-EVAR) and for elective patients (el-EVAR). Still, due to higher anatomical complexity more graft-related complications may arise in r-EVAR patients. Methods: MEDLINE databases were searched to identify publications reporting on outcomes after r-EVAR and el-EVAR. Landmark EVAR randomized controlled trial results were used as comparison. Results: After-discharge outcomes (other than mortality), were reported in 5 studies including 509 r-EVAR patients. A direct comparison between r-EVAR and el-EVAR patients was found in 2 studies, including 2895 patients (256 r-EVAR and 2653 el-EVAR). Type I endoleak rates ranged from 5.4-21% in r- EVAR and from 4.4-10% el-EVAR. Rates of secondary intervention in r-EVAR ranged between 16.7-76% and in el-EVAR from 11-27.7%. Five year rate of complications after r-EVAR inside instructions for use were 8.8% and reinterventions were 16.7%. Conclusions: r-EVAR patients present higher rates of type I endoleaks and secondary interventions. However, when complying with IFU, aneurysm-related complications overlap to the el-EVAR patients. Surveillance strategies should be tailored according to the baseline anatomical complexity and early complications and not to the timing of repair.